Silk. Series one - Stuke, Neil; Penry-Jones, Rupert, 1970-; Peake, Maxine; Hughes, Tom, 1986-; Dormer, Natalie, 1982-; MacMillan, John; Sosanya, Nina; Offer, Michael; Evans, David; Morshead, Catherine; Moffat, Peter, 1962-; Thompson, Steve (Stephen); et al. (Burbank, CA : Distributed in the USA and Canada by Warner Home Video, Inc., 2013)
Martha Costello is a brilliant, passionate defense barrister with a reputation for defending the poor and downtrodden. She is about to embark on the next step of her career and apply to be a member of the highly prestigious Queen's Counsel. But she's not the only one at her chambers applying. Joining Martha is Clive Reader - charming and ruthless, funny, gifted, and dangerous. Only one is likely to be made QC, so how they perform in court is vital, and Clive knows how to play the game.
Title from web page.
Originally broadcast as a television series in 2011.
Special features: Behind the scenes.
Neil Stuke, Rupert Penry-Jones, Maxine Peake, Tom Hughes, Natalie Dormer, John Macmillan, Nina Sosanya.
DVD; region 1, NTSC; anamorphic widescreen; Dolby Digital.
Keywords: Criminal defense lawyers -- England -- Drama; Television series; Television serials